Relationship between disease activity and patient-reported outcomes in rheumatoid arthritis: Post hoc analyses of overall and Japanese results from two phase 3 clinical trials. Issue 6 (2nd November 2018) - Ishiguro, Naoki; Dougados, Maxime; Cai, Zhihong; Zhu, Baojin; Ishida, Masato; Sato, Masayo; Gaich, Carol; Quebe, Amanda; Stoykov, Ivaylo; Tanaka, Yoshiya
Abstract: Objective: To examine patient-reported outcomes (PROs) in patients with different rheumatoid arthritis (RA) disease activity levels and identify residual symptoms. Methods: Post hoc analyses of overall and Japanese data from two randomized controlled trials including RA patients with previous inadequate responses to methotrexate (NCT01710358) or no/minimal previous disease-modifying antirheumatic drug treatment (NCT01711359) (sponsor: Eli Lilly and Company). Week 24 assessments were disease activity (Simplified Disease Activity Index, Disease Activity Score/Disease Activity Score 28 joints-erythrocyte sedimentation rate) and PROs (pain visual analog scale [VAS], morning joint stiffness [MJS], Health Assessment Questionnaire-Disability Index, Functional Assessment of Chronic Illness Therapy-Fatigue, and Medical Outcomes Study Short Form 36 Health Survey Physical and Mental Component Scores). Results: Patients achieving remission/low disease activity (LDA) at Week 24 had larger/significant improvements from baseline in pain, MJS, disability, fatigue, and physical and emotional quality of life versus patients with high/moderate disease activity. Some patients achieving remission and LDA, reported residual pain (pain VAS >10 mm): 20.8–39.3% and 48.7–70.0% (overall study populations), 16.0–34.5% and 47.1–62.0% (Japanese patients). Residual MJS and fatigue were also reported. Conclusion: Remission/LDA were associated with improvements in PROs in overall and Japanese patient populations; however, some patients achieving remission had residual symptoms, including pain.